Korelasi antara Lingkungan Belajar dan Minat Belajar Siswa dengan Hasil Belajar Matematika - N P E Arya Pratiwi; i made suarjana; ndara tanggu renda (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the correlation between the learning environment with the results of learning Mathematics Students, Correlation between Learning Interest with the results of learning mathematics Students, and Correlation Between Learning Environment and Student Learning Interest with Student Math Learning Results. Type of this research is research Expost Facto population that is student of SDN Gugus I District of East Denpasar which amounted to 146 students taken a number 97 as sample. With analysis technique of descriptive and inprensial statistic that is T Test. From result of analysis (1) Result of descriptive analysis found that learning environment is in high category 46,39%, Interest in study is in very high category 59,79%, and result of learning mathematics is in good category 95,88%. (2) learning environment is real and positive relation with mathematics learning result shown because t count (5,479)> t - table (1,667). (3) interest in learning a real and positive relationship with mathematics learning results is shown because t-count (6,625)> t - table (1.667). (4) There is a positive relationship between learning environment, and interest in learning with mathematics learning results can be seen that r count 0.610> r table 0.194 as well as test results with the test f (simultaneously) with Î± = 5% it can be seen that the learning environment, and interest in learning are simultaneously significantly related to mathematics learning outcomes